2015
DOI: 10.1121/1.4922012
|View full text |Cite
|
Sign up to set email alerts
|

Informational masking of speech in dyslexic children

Abstract: Studies evaluating speech perception in noise have reported inconsistent results regarding a potential deficit in dyslexic children. So far, most of them investigated energetic masking. The present study evaluated situations inducing mostly informational masking, which reflects cognitive interference induced by the masker. Dyslexic children were asked to identify a female target syllable presented in quiet, babble, unmodulated, and modulated speech-shaped noise. Whereas their performance was comparable to norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…Unlike previous results obtained in SN/GN ) and babble noise (Hazan et al, 2013), our results failed to reveal any group difference on the perception of any of the phonetic traits investigated. However, this result is coherent with recent observations that noise seems to affect dyslexic children's reception of voicing, place and manner of articulation in the same way as it affects normally reading children (Calcus et al, 2015b;Calcus et al, 2016).…”
Section: Are All Phonetic Features Affected To the Same Extent?supporting
confidence: 90%
See 3 more Smart Citations
“…Unlike previous results obtained in SN/GN ) and babble noise (Hazan et al, 2013), our results failed to reveal any group difference on the perception of any of the phonetic traits investigated. However, this result is coherent with recent observations that noise seems to affect dyslexic children's reception of voicing, place and manner of articulation in the same way as it affects normally reading children (Calcus et al, 2015b;Calcus et al, 2016).…”
Section: Are All Phonetic Features Affected To the Same Extent?supporting
confidence: 90%
“…Interestingly, in the present study, dyslexic children were also impaired when presented with Babble noise, hence underscoring the importance of higher-level, cognitive factors to their SIN perception deficit. Recent work in dyslexic children points to specific difficulties in auditory backgrounds maximizing IM (Calcus, Colin, Deltenre, & Kolinsky, 2015a, 2015b). Yet so far, the outcome of studies investigating IM in dyslexic individuals is mixed, which could be due to differences in the populations investigated across studies.…”
Section: What Is the Nature Of The Speech In Noise Deficit In Dyslementioning
confidence: 99%
See 2 more Smart Citations
“…While this deficit is less noticeable in optimal listening conditions (e.g., speech-in-quiet), it becomes more evident in challenging listening conditions. Several studies have found that speech-in-noise perception is impaired in both children and adults with DD (Boets et al, 2011;Calcus, Colin, Deltenre, & Kolinsky, 2015;Dole, Hoen, & Meunier, 2012;Dole, Meunier, & Hoen, 2014;Ziegler, Pech-Georgel, George, & Lorenzi, 2009).…”
Section: Introductionmentioning
confidence: 99%